Androecium development of Oxypetalum appendiculatum Mart. (Apocynaceae): A Taxonomic Approach - F. A. Z. Vital; A. T. Nakamura (Scientific Electronic Archives, 2018)
Circa 80% of the neotropical species of Asclepiadoideae (Apocynaceae) belong to the “MOOG Clade”, whose interrelations are poorly established. This study describes the floral morphology, anther development, microsporogenesis, microgametogenesis, and pollinarium and pollen grain morphology of Oxypetalum appendiculatum to foster future taxonomic work. In addition to typical morphological features of Asclepiadoideae, as a bifid vinaceous appendix and a translator with a laterally expanded retinaculum, flowers present a clear division of stamens into three groups, with respect to size and arrangement in the flower, which has not yet been reported in the literature. Stamens present connate, subsessile filaments, bisporangiate anthers with six parietal layers, and dicotyledonous development. Endothecium is unthickened; secretory tapetum is biseriate on the adaxial side and multiseriate on the abaxial surface. Successive microsporogenesis produces linear tetrads. Single pollen grains, united in pollinia, are tricellular and inaperturate. Features as bisporangiate anthers and successive microsporogenesis delimit the subfamily. Unthickened endothecium may indicate a derived position of O. appendiculatum in the “MOOG Clade”.